Abortion Ban in English Social Media in 2022: Pragmatic Linguistics of Online Communications - Anna A. Gnedash; Veronika V. Katermina (Виртуальная коммуникация и социальные сети)
The present research featured the conflict discourse of online communication in social networks on the topic of abortion ban. The empirical base included 3,000,000 Twitter messages in English. The sampling by keywords women and abortion covered the period from May 1 to July 31, 2022, which saw an outburst of online and offline civic activities regarding some national anti-abortion policies. The resulting web corpus of network linguistic data (datasets) was subjected to multidimensional analysis using such methods as Data Science, mathematical modeling, relational sociology, corpus analysis, discourse analysis, etc. All these procedures combined resulted in a multidimensional comprehensive analysis of the simulated English asynchronous multimodal discursive field in Twitter. The models made it possible to visualize online communications in social networks, as well as to describe the discourse of online communication between pro-choice and pro-life. The authors analyzed the pragmatic potential of network communities on the current political agenda. The method might help to identify the conflict potential that can evolve from online communication into offline socio-political actions.